2022
DOI: 10.1007/s12672-022-00553-7
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-derived exosomal HOTAIRM1 regulates SPON2 in CAFs to promote progression of lung adenocarcinoma

Abstract: Objective SPON2 is one of the extracellular matrix proteins, which is closely related to the progression of a variety of tumors including non-small cell lung cancer (NSCLC), but its upstream regulation mechanism remains unclear. Our research aims to find the specific regulatory pathway of SPON2 by exploring the potential crosstalk between tumor cells and cancer-associated fibroblasts (CAFs) in tumor microenvironment (TME) of NSCLC. Methods We analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Ming Wu et al(2023) found that SPON2 promotes the bone metastasis of lung adenocarcinoma via activation of the NF-κB signaling pathway. [45] According to Chen et al, [46] Tumorderived exosomes HOTAIRM1 can transfer to CAFs, regulate the expression of SPON2 in CAFs cells, and ultimately promote the progression of NSCLC. According to Ni et al, [47] SPON2 silencing inhibited the proliferation of LSCC cells through inhibiting the activation of PI3K/AKT signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Ming Wu et al(2023) found that SPON2 promotes the bone metastasis of lung adenocarcinoma via activation of the NF-κB signaling pathway. [45] According to Chen et al, [46] Tumorderived exosomes HOTAIRM1 can transfer to CAFs, regulate the expression of SPON2 in CAFs cells, and ultimately promote the progression of NSCLC. According to Ni et al, [47] SPON2 silencing inhibited the proliferation of LSCC cells through inhibiting the activation of PI3K/AKT signaling.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study only analyzed T1 stage samples from TCGA for LUAD. A comprehensive analysis of changes in SPON2 expression across all stages of lung cancer would provide a more robust diagnostic foundation for the diagnosis and treatment of this disease ( 40 ).…”
Section: Spon2 As a Broad-spectrum Biomarker In Different Diseasesmentioning
confidence: 99%
“…A specific example is exosomal HOTAIRM1, which has been observed to modulate the expression of SPON2, an extracellular matrix protein, in cancer-associated fibroblasts. This modulation promotes cancer cell migration and invasion [ 98 ]. Additionally, PCAT6 derived from NSCLC exosomes influences macrophages polarization, promoting the shift towards M2 phenotypes that support tumor growth [ 99 ].…”
Section: Lncrnas As Biomarkers In Nsclcmentioning
confidence: 99%